The Relationship Between Corruption and Foreign Direct Investment Inflows in Turkey: An Empirical Examination - M. Umur TOSUN; M. Onur YURDAKUL; Pelin VAROL İYIDOĞAN (Transylvanian Review of Administrative Sciences, 2014)
In the corruption literature, most of the studies indicate that corruption has adverse effects on the investment environment and thus it diminishes foreign direct investment (FDI) inflows. However, regarding the so-called adverse effects between FDI and corruption, it is noticed that some studies reached to conclusions in the opposite direction. In this study, the causality relationship among corruption, political risk, industrial production index (as a proxy to gross domestic product) and FDI entrance variables for Turkey over the period 1992M01-2010M12 is analyzed by means of Pesaran, Shin and Smith (2001) bounds test approach of cointegration and error correction methods. As a result, it is found that corruption has distortive effects on FDI in Turkey both for short and long run periods and this indicates that ‘helping hand’ corruption does not exist in Turkey. In addition, in the long run, FDI increases with raising income. Contrary to the expectations, it is detected that increase in political risk contributes to FDI inflows in the short run.